2007
DOI: 10.1103/physrevb.76.174515
|View full text |Cite
|
Sign up to set email alerts
|

Exact analytical solution of the problem of current-carrying states of the Josephson junction in external magnetic fields

Abstract: The classical problem of the Josephson junction of arbitrary length W in the presence of externally applied magnetic fields (H) and transport currents (J) is reconsidered from the point of view of stability theory. In particular, we derive the complete infinite set of exact analytical solutions for the phase difference that describe the current-carrying states of the junction with arbitrary W and an arbitrary mode of the injection of J. These solutions are parameterized by two natural parameters: the constants… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…(2)-(4) are consistent with other models of Josephson junction networks previously studied in [17,24,30,31]. Exact solutions of Eq.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…(2)-(4) are consistent with other models of Josephson junction networks previously studied in [17,24,30,31]. Exact solutions of Eq.…”
Section: Introductionsupporting
confidence: 87%
“…Exact solutions of Eq. (1) on a finite interval have been obtained earlier in [17,30,31,34] for different special cases. Here, we use an approach similar to that of the Refs.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Instead, for a magnetic field above the critical value, i.e., for H(t) > 2, solitons in the form of fluxons penetrate the LJJ from its ends. However, in this case at a specific value of the magnetic field several solutions, describing distinct configurations with different amount of solitons, may concurrently exist 51,[53][54][55] . The dynamical approach is essential to describe the JJ state when multiple solutions are available.…”
Section: /14mentioning
confidence: 99%
“…Nevertheless, for H(t) = 0 no solitons actually remain within the system in both forward and backward dynamics. This hysteretical behavior comes from the multistability of the SG model 33,51,[53][54][55][56] . In fact, Kuplevakhsky and Glukhov demonstrated that each solution of the SG equation, with a distinct number of solitons, is stable in a broad range of magnetic field values [53][54][55] .…”
Section: /14mentioning
confidence: 99%